Biodiversity of mycotoxigenic aspergillus species in Egyptian peanuts and strategies for minimizing aflatoxin contamination - Sultan, Yousef Yasseen Abdel-Rahmin (Cranfield University, 2010)
Peanuts are an important crop grown in Egypt for either local consumption or export to European markets. The present study examined the importance of mycotoxigenic Aspergilli in Egyptian peanuts from five different regions (Alexandria, El-Beheira, El- Daqahliya, El-Sharqiya, Asyut) in two seasons (2007, 2008). This led to consideration of different potential strategies to control aflatoxigenic A. flavus strains and associated aflatoxin contamination of peanuts. The most common species in peanuts were from Aspergillus section Flavi, Aspergillus section Nigri and Aspergillus section Circumdati. Both qualitative (coconut cream agar) and quantitative analyses (HPLC) were used to analyse the potential mycotoxin production by strains isolated from peanuts. Of a total of 88 Aspergillus section Flavi strains examined, 90% were aflatoxigenic. Cont/d.